The role of small extracellular vesicle non-coding RNAs in kidney diseases - Luo, Chuxuan; Liu, Haojie; Shao, Lina; Tang, Jiyu; He, Qiang; Jin, Juan (Frontiers in Genetics, 2022)
Kidney diseases have become an increasingly common public health concern worldwide. The discovery of specific biomarkers is of substantial clinical significance in kidney disease diagnosis, therapy and prognosis. The small extracellular vesicle (sEV) can be secreted by several cell types, like renal tubular epithelial cells, podocytes, collecting duct cells and leap cells, and functions as a communication medium between cells by delivering signaling molecules, including proteins, lipids and nucleic acids. There has been growing evidence that kidney diseases are associated with aberrant expression of sEV-derived non-coding RNAs (sEV-ncRNAs). As a result, sEV-ncRNAs may provide valuable information about kidney diseases. In this paper, a systematic review is presented of what has been done in recent years regarding sEV-ncRNAs in kidney disease diagnosis, treatment and prognosis.